Knowledge, attitude and practice of hypertension among hypertensive patients in a tertiary care teaching hospital - J., Rajan; M., Sakthibalan; Marshall Raj, Gerard; A., Mangaiarkkarasi (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Hypertension is a chronic disease and an important risk factor for cardiovascular complications. The increase in prevalence of hypertension is attributed to age of population, urbanization, sedentary habits, lack of physical activity, obesity, alcohol consumption and exposure to continuous stress. Regular anti-hypertensive medications can reduce the long-term risk of cardiovascular morbidity and mortality. This study was done to assess the knowledge, attitude and practice regarding hypertension and to assess the drug compliance in hypertensive patients. Methods: This study was a cross sectional questionnaire based, conducted among 200 hypertensive patients attending hypertension clinic (Department of Medicine) of Sri Venkateshwaraa Medical College Hospital and Research Centre, Puducherry, India from October to December 2018. A close-ended questionnaire was given to the patients, which comprised of 16 questions on knowledge (5), attitude (5) and practice (6). Data was analyzed and expressed in descriptive statistics. Results: The commonly prescribed anti-hypertensive medications were calcium channel blockers (79%) and β blockers (26.5%). Knowledge regarding hypertension, normal BP, symptoms and complications was 74%, 54.5%, 41.5% and 37.5% respectively. Positive attitude regarding regular medications, role of drugs, diet control, salt restriction and physical activity was found in 94%, 40.5%, 74%, 76% and 67% respectively. Regular BP measurement, follow up, salt restriction and exercise were practiced by 77%, 77%, 72% and 9% of patients respectively. Conclusions: Present study reflected a lack of knowledge among hypertensive patients regarding normal BP, symptoms and complications. A positive attitude and practice were observed among the patients except for practice of regular exercise. Hence, emphasize on awareness about symptoms, complications and importance of physical activity should be improved particularly among male patients.